Orderly retire China's coal-fired power capacity via capacity payments to support renewable energy expansion - Guangzhi Yin; Bo Li; Natalie Fedorova; Patricia Hidalgo-Gonzalez; Daniel M. Kammen; Maosheng Duan (iScience, 2021)
Summary: The energy-only-market implemented in China cannot strongly support large-scale renewable energy expansion because the renewable energy expansion may disorderly phase out non-renewable power capacity. However, non-renewable power capacity, particularly the coal-fired power capacity in China, can provide vital power system adequacy needed by renewable energy expansion. We introduce capacity payments to orderly retire current coal-fired power capacity by transforming some of it into reserve capacity in order to support renewable energy expansion. Using generation and transmission expansion results from the SWITCH-China model, this paper proposes an orderly retirement path based on the assumption of implementing capacity payments. Our results show that roughly 100–200 gigawatts (GW) of coal-fired power capacity can continue to serve through 2050, and most of it is used as reserve capacity. Capacity payments of 400–700 billion yuan are needed to achieve this retirement path, and a higher adequacy requirement needs higher payments.